In-Vitro Antimicrobial Drug Susceptibility Pattern of Methicillin Resistant Staphylococcus Aureus (MRSA) - Mubariz, Rabia; Yasmin, Shahina; Taj, Shazia; Butt, Tariq; Ellahi, Ayesha; Mussarat, Uzma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the in-vitro antimicrobial susceptibility pattern of Methicillin-resistant Staphylococcus aureus (MRSA) isolates using an automated VITEK-2 compact system.Study Design: Cross-sectional study.Place and Duration of Study: Pakistan Railway Hospital (PRH) Rawalpindi collaborates with the Armed Forces Institute of Pathology (AFIP) Rawalpindi, from Sep 2018 to Aug 2019.Methodology: 100 MRSA samples were isolated from tissue, pus, urine, blood, high vaginal swabs (HVS) and ear swabs using standard microbiological techniques. MRSA isolates' antimicrobial susceptibility pattern was made using an automated VITEK-2 compact system.Results: Among 100 MRSA isolates, 63% were obtained from pus and 17% from tissue, respectively. MRSA isolates showed 100% sensitivity to Vancomycin, Teicoplanin and Linezolid. Susceptibility to other drugs has shown wide variation, i.e., Tigecycline 97%, Rifampicin 95%, Clindamycin 86%, Tetracycline 79%, and Cotrimoxazole 78%. The minimum inhibitory concentration (MICs) of Vancomycin and Linezolid against MRSA isolates revealed that 41% had 0.5 µg/ml, 46% had one µg/ml, and 13% had two µg/ml for Vancomycin. Whereas for Linezolid, 38 isolates had MIC 1 µg/ml, then 62 isolates had MIC 2 µg/ml.Conclusion: All the isolates showed 100% sensitivity to Vancomycin, Teicoplanin and Linezolid. Moreover, being less costly, Clindamycin, Tetracycline and Cotrimoxazole are good oral choices for empirical therapy against minor MRSA infections.